An antibacterial composite film based on cellulose acetate/TiO2 nanoparticles. (23rd November 2020) - Gao, Ying; Wang, Xiu; Li, Xiang; Dai, Hongqi
Abstract : The aims of this paper were: (1) prevent the aggregation of TiO2 nanoparticles and obtain a uniform suspension; (2) obtain homogeneous composite films through three simple steps; (3) evaluate the antibacterial properties of CA/TiO2 composite films against E. coli . Abstract : In this study, cellulose acetate (CA)/titanium dioxide (TiO2 ) composite films with different loadings (4 wt%–12 wt%) were prepared by the combination of ultrasonic dispersion, stirring and hot-pressing processes. Some properties of the films were characterized by techniques including SEM, XRD, FTIR spectroscopy, WCA analysis, tensile strength measurement, TGA, DSC and antibacterial analysis. The morphology and Ti element analysis mapping of the composite films were investigated through the methods of SEM. The results showed that the TiO2 nanoparticles were successfully and uniformly connected with cellulose acetate. With the increase of TiO2 content, the hydrophilic property of the films was enhanced. Films with different contents also maintained thermal stability and mechanical properties. The CA/TiO2 film with 12 wt% loading exhibited good antibacterial activity against Escherichia coli with 55.6% sterilization in 12 h. Therefore, the CA/TiO2 composite films can be applied as antibacterial films prepared by a simple method.